Inverse Kinematics Optimization Method of a 6-DOF Robot - Jian Wang; Yu Ao (Jixie chuandong)
The inverse kinematics solution of the traditional 6-axis robot requires position information and attitude information. Aiming at the problem of difficulty and uncertainty of object attitude recognition， a 6-axis robot attitude solution algorithm based on object position information is proposed. Based on the concept of robot dexterity， a service ball model for the robot's 5th axis is established， and the end positions of the robot are discretized to obtain a series of discrete points on the service sphere. Based on the conformal geometry of the robot， the mapping relationship between the discrete points and the joint angle of the robot is studied， and the attitude set of the robot at a certain spatial position is obtained. According to the comprehensive criteria of robot singularity， joint avoidance and joint continuity， a set of best robot poses is selected from the pose set. In the Cartesian coordinate system， interpolation of different position points is performed， and the continuous motion between different position points of the robot is realized by solving the pose of different interpolation points. The results show that， according to the three-dimensional coordinate information of the object， the inverse kinematics calculation of the 6-axis robot can be completed and the calculation speed is fast and the accuracy is high， which simplifies the attitude recognition process of the object and improves the efficiency of the robot's continuous operation.